Anti-Myocardial Ischemia Reperfusion Injury Mechanism of Dried Ginger-Aconite Decoction Based on Network Pharmacology - Feng Xie; Yuan-Yuan Wu; Guang-Jing Duan; Bin Wang; Feng Gao; Pei-Feng Wei; Lin Chen; A-Ping Liu; Min Li (Frontiers Media S.A., 2021)
Dried ginger-aconite decoction (DAD) is a traditional Chinese medicine (TCM) formula that has been extensively used in the treatment of myocardial ischemia reperfusion injury (MI/RI). However, its specific mechanism against MI/RI has not been reported yet. Therefore, this paper studies the potential active components and mechanism of DAD against MI/RI based on network pharmacology and experimental verification. Sixteen active components of DAD were screened according to oral bioavailability and drug similarity indices. Through Cytoscape 3.7.0, a component-target network diagram was drawn, and potential active components of DAD against MI/RI were determined. Protein-protein interaction (PPI) and compound-target-pathway (C-T-P) networks were established through the software to discover the biological processes, core targets and core pathways of DAD against MI/RI. High Performance Liquid Chromatography (HPLC) analysis identified the presence of potentially active core components for network pharmacological prediction in DAD. It was found that DAD might have played a therapeutic role in anti-MI/RI by activating the PI3K/Akt/GSK-3β signaling pathway in order to reduce mitochondrial hypoxia injury and myocardial cell apoptosis. The network pharmacological prediction was validated by Hypoxia/reoxygenation(H/R) model in vitro and ligation model of the ligation of the left anterior descending branch in vivo. It was verified that DAD had activated PI3K/AKT/GSK-3β to reduce myocardial apoptosis and play a therapeutic function in MI/RI.